PROBLEMATIKA PEMBERLAKUAN QUICK RESPONSE CODE INDONESIA STANDARD BAGI KEMAJUAN EKONOMI DIGITAL PELAKU USAHA UMKM - Megananda Aruna Dewanty; Imron Mustofa (Jurnal Ekonomi & Bisnis, 2023)
The Quick Response Code Standard (QRIS) has become the most important innovation in digital payment systems, influencing various economic aspects. This research uses descriptive qualitative methods with literature study techniques. The aim of this research is to study the basic concepts of QRIS and study the practicalities of implementing a digital payment system for business actors. With QRIS, it can facilitate electronic payments with QR codes that can be widely used. The implementation of the QRIS digital payment system not only provides many benefits in terms of ease of transactions, but there are still problems faced, such as network problems which make the transaction process hampered; the complicated registration process makes some business actors give up their intention to register; it is feared that the increase in MDR rates for micro business actors will reduce income for sellers; the rise of fake QRIS code fraud makes people worried about carrying out digital transactions; not all of the storage memory on cell phones used by the public can accommodate the existing update capacity; the uneven distribution of merchants makes it difficult for people who use digital wallets; and the lack of understanding of the Indonesian people makes QRIS transactions difficult to develop.. This research provides a broader understanding of the usefulness of QRIS for business actors and the economy as a whole.